2016
DOI: 10.3906/tar-1607-57
|View full text |Cite
|
Sign up to set email alerts
|

Changes in berry quality of northern highbush blueberry(Vaccinium corymbosum L.) during the harvest season

Abstract: As blueberries ripen successively and are commercially harvested over a period of several weeks, their composition may be altered during the harvest. The aim of this study was to compare blueberry fruit composition during the entire harvest season. Fully ripe fruits of two northern highbush blueberry cultivars (Bluecrop and Jersey) were harvested weekly at two different locations. Additionally, the Earliblue cultivar was monitored at a single location. Most of the examined characteristics changed during the ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
57
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 34 publications
(86 reference statements)
9
57
1
Order By: Relevance
“…Mert and Erturk (2017) reported the crude fat amount chestnut cultivars ranged from 0.87 to 2.61%. Our results are in accordance with those obtained by Erturk et al (2006) for C. sativa and hybrid cultivars, for Italian cultivars (Sacchetti and Pinnavaia, 2005) and for Spanish cultivars (De La Montana Miguelez et al, 2004 andPereiraLorenzo et al, 2006) Previous studies indicated cultivar/genotype differences on chemical content of fruit species, including stone fruits, nuts, berries and subtropical fruits (Celik et al, 2007;Ercisli, 2009;Ercisli et al, 2010;Erturk et al, 2010;Saridas et al, 2016;Yazici and Sahin, 2016;Zorenc et al, 2016).…”
Section: Proximate Compositionsupporting
confidence: 81%
“…Mert and Erturk (2017) reported the crude fat amount chestnut cultivars ranged from 0.87 to 2.61%. Our results are in accordance with those obtained by Erturk et al (2006) for C. sativa and hybrid cultivars, for Italian cultivars (Sacchetti and Pinnavaia, 2005) and for Spanish cultivars (De La Montana Miguelez et al, 2004 andPereiraLorenzo et al, 2006) Previous studies indicated cultivar/genotype differences on chemical content of fruit species, including stone fruits, nuts, berries and subtropical fruits (Celik et al, 2007;Ercisli, 2009;Ercisli et al, 2010;Erturk et al, 2010;Saridas et al, 2016;Yazici and Sahin, 2016;Zorenc et al, 2016).…”
Section: Proximate Compositionsupporting
confidence: 81%
“…Pomological features of berries are highly influenced by the species and variety within species and the ecological conditions of the plants Veberic et al, 2015). Despite a great range of researches conducted as comprehensive studies on fruit properties of blueberries (Smolarz, 2006;Beccaro et al, 2006;Celik, 2009;Giovanelli and Buratti, 2009;Zorenc et al, 2016), the knowledge available on bilberries is scarce.…”
Section: Total Anthocyanin Contentmentioning
confidence: 99%
“…Fruit species have been used not only for nutrition purposes but also to meet personal and social needs such as curing diseases, beautifying the planet, etc. (Hegedus et al 2010, Canan et al 2016, Sorkheh and Khaleghi 2016, Zorenc et al 2016.…”
Section: Introductionmentioning
confidence: 99%